2017
DOI: 10.1016/j.ejogrb.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after Uphold™ Vaginal Support System surgery for apical pelvic organ prolapse—A prospective multicenter study

Abstract: Objective: To study the effects on quality of life in women operated for apical pelvic organ prolapse using the Vaginal Uphold TM System. Study design: In this prospective cohort study, women (n = 207) with symptomatic apical prolapse, with or without cystocele, were operated using the Uphold TM Vaginal Support System. Follow-up for quality of life was performed at 12 months after surgery, and assessed by the PFDI-20, and PFIQ-7, and sexual function by the PISQ-12. We used odds ratios (ORs) with 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
3
18
1
4
Order By: Relevance
“…Previous studies involving the Uphold LITE mesh kit treatment of prolapse have reported a 12‐month success rate of 94% for the apical compartment and 71% for all compartments; the rate of serious complications was 4.3% . Rahkola‐Soisalo et al reported a success rate of 97.5% for the apical compartment and 78% for the anterior compartment at 5‐year follow‐up. The lower success rate in the current study might be explained by the use of a composite endpoint included both anatomic and subjective success plus no reintervention.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies involving the Uphold LITE mesh kit treatment of prolapse have reported a 12‐month success rate of 94% for the apical compartment and 71% for all compartments; the rate of serious complications was 4.3% . Rahkola‐Soisalo et al reported a success rate of 97.5% for the apical compartment and 78% for the anterior compartment at 5‐year follow‐up. The lower success rate in the current study might be explained by the use of a composite endpoint included both anatomic and subjective success plus no reintervention.…”
Section: Discussionmentioning
confidence: 97%
“…The Uphold LITE mesh kit is a third generation kit comprising a two arm, lightweight polypropylene mesh with a decreased biomaterial load to avoid mesh‐related complications. Some studies reported high success rates with a relatively low rate of complications . Nevertheless, the advantages and disadvantages of transvaginal mesh surgery are still debated and further studies are needed to confirm these results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The better QoL scores compared to baseline scores were also observed in all the 3 P-QoL components (PC, PSC and PRC) after 6 months. Previous studies in Western countries using P-QoL instrument also con rmed that correction of POP via alloplastic vaginal meshes can signi cantly improve patients' QoL [24,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 84%
“…Rahkola-Soisalo et al [38] have also studied the role of the influence of the isolated apical defect surgery on the quality of life of the patients. 207 patients were qualified for their study, and they had an isolated apical defect procedure performed using the Vaginal Uphold™ system.…”
Section: Discussionmentioning
confidence: 99%